2017
DOI: 10.1038/s41598-017-16393-3
|View full text |Cite
|
Sign up to set email alerts
|

Resident Microbiome Disruption with Antibiotics Enhances Virulence of a Colonizing Pathogen

Abstract: There is growing evidence that symbiotic microbes play key roles in host defense, but less is known about how symbiotic microbes mediate pathogen-induced damage to hosts. Here, we use a natural wildlife disease system, house finches and the conjunctival bacterial pathogen Mycoplasma gallisepticum (MG), to experimentally examine the impact of the ocular microbiome on host damage and pathogen virulence factors during infection. We disrupted the ocular bacterial community of healthy finches using an antibiotic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…Initial studies in mice suggested that the presence of the ocular microbiome regulates the composition of the tear film, possibly impacting bacterial ability to adhere and infect the conjunctiva . Furthermore, evidence exists to support the beneficial effect of the ocular microbiota in preventing keratitis and other infectious ocular conditions . Characterization of a bacterial community beneficial to ocular surface health may lead to the development of novel therapies to mitigate bacterial disbyosis and conditions associated with it, and should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies in mice suggested that the presence of the ocular microbiome regulates the composition of the tear film, possibly impacting bacterial ability to adhere and infect the conjunctiva . Furthermore, evidence exists to support the beneficial effect of the ocular microbiota in preventing keratitis and other infectious ocular conditions . Characterization of a bacterial community beneficial to ocular surface health may lead to the development of novel therapies to mitigate bacterial disbyosis and conditions associated with it, and should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health(Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017). dysbiosis of the microbiota may be monitored as an early warning sign about potential downstream effects on host ecology and health(Bahrndorff, Alemu, Alemneh, & Lund Nielsen, 2016;Cheng et al, 2015;Lemieux-Labonté, Simard, Willis, & Lapointe, 2017;Thomason, Mullen, Belden, May, & Hawley, 2017).…”
mentioning
confidence: 99%
“…) in mice; and against the conjunctival bacterial pathogen Mycoplasma gallisepticum in house finches (Thomason et al. ). Furthermore, the role of individual defensive symbionts on host fitness has been demonstrated both empirically (Vorburger and Perlman ) and theoretically (King and Bonsall ).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative framing provides one possible approach to testing the resulting predictions. Evidence for protective effects of the microbiome exists across a range of hosts, including against Pseudomonas syringae in horse chestnut trees (Koskella et al 2017b), tomato (Berg and Koskella 2018), and Arabidopsis plants (Innerebner et al 2011); against both salmonella (Kubinak et al 2015) and intestinal infection with Entamoeba histolytica (Watanabe et al 2017) in mice; and against the conjunctival bacterial pathogen Mycoplasma gallisepticum in house finches (Thomason et al 2017). Furthermore, the role of individual defensive symbionts on host fitness has been demonstrated both empirically (Vorburger and Perlman 2018) and theoretically (King and Bonsall 2017).…”
Section: Discussionmentioning
confidence: 99%